Regional Intraosseous Administration of Prophylactic Antibiotics is More Effective Than Systemic Administration in a Mouse Model of TKA. Issue 11 (November 2015) - Young, Simon W.; Roberts, Tim; Johnson, Sarah; Dalton, James P.; Coleman, Brendan; Wiles, Siouxsie
Abstract: Background: In human TKA studies, intraosseous regional administration (IORA) of prophylactic antibiotics achieves local tissue antibiotic concentrations 10 times greater than systemic administration. However, it is unclear if such high concentrations provide more effective prophylaxis. Questions/purposes: We asked: (1) What prophylaxis dosage and route (intravenous [IV] versus IORA of prophylactic antibiotics) produce less in vivo bacterial burden compared with no‐antibiotic controls? (2) Compared with controls, what prophylaxis dosage and route yield fewer colony‐forming units (CFUs) in euthanized animals in a model of TKA? (3) Is prophylactic IORA of antibiotics more effective than same‐dose IV antibiotic administration in reducing CFUs? Methods: Mice (six to nine per group) were block randomized to one of six prophylaxis regimens: control, systemic cefazolin (C100IV ), IORA of cefazolin (C100IORA ), systemic vancomycin (V110IV ), low‐dose systemic vancomycin (V25IV ), and low‐dose IORA of vancomycin (V25IORA ). Surgery involved placement of an intraarticular knee prosthesis, followed by an inoculum of bioluminescent Staphylococcus aureus strain Xen36. Biophotonic imaging assessed in vivo bacterial loads, and after 4 days bacterial load was quantified using culture‐based techniques. Comparisons were made for each prophylactic regimen to controls and between same‐dose IV and IORA of prophylactic antibiotic regimens. Results: Mice treated with systemic high‐dose vancomycin, IORA of vancomycin, or IORA of cefazolin had lower in vivo Staphylococcus aureus burdens (median area under curve, Control: 5.0 × 10 6 ; V110IV : 1.5 × 10 6, difference of medians 3.5 × 10 6, p = 0.003; V25IV : 1.94 × 10 6, difference 3.07 × 10 6, p = 0.49; V25IORA : 1.51 × 10 6, difference 3.5 × 10 6, p = 0.0011; C100IORA : 1.55 × 10 6, difference 3.46 × 10 6, p = 0.0016; C100IV : 2.35 × 10 6, difference 2.66 × 10 6, p = 0.23.) Similar findings were seen with culture‐based techniques on recovered implants. IORA of prophylactic antibiotics was more effective than same‐dose IV administration in reducing bacterial load on recovered implants (median CFUs < 7.0 × 10 0 vs 2.83 × 10 2, p = 0.0183). Conclusions: IORA of prophylactic cefazolin and vancomycin was more effective than the same dose of antibiotic given systemically. The effectiveness of vancomycin in particular was enhanced by IORA of prophylactic antibiotics despite using a lower dose. Clinical relevance: Our study supports previous studies of IORA of prophylactic antibiotics in humans and suggests this novel form of administration has the potential to enhance the effectiveness of prophylaxis in TKA. Because of concerns regarding antibiotic stewardship, IORA of prophylactic vancomycin may be more appropriately restricted to patients having TKA who are at greater risk of infection, and clinical trials are in progress.